Role Of Ultrasound For The Diagnosis Of Complications Of Dengue Fever In Gujrat - Islam, Mahnoor; Afsar, Rehan; Ali, Abid; Haider Naqvi, Faizan (Medical Science Journal for Advance Research, 2022)
Background : The purpose of this study is to evaluate if ultrasonography may be used as an useful addition to clinical and radiology profiles in diagnosing dengue fever and predicting virus severity by comparing imaging findings. The difference in sonographic characteristics observed in patients of various ages was also investigated. Objective : The goal of this study is to determine role of ultrasound for diagnosis of complications of dengue fever in Gujrat Materials and Methods: This is a retrospective study. From October and December 2021, 79 patients who were serologically confirmed with dengue fever were referred for ultrasound scanning of the abdomen at Aziz bhatti shaheed hospital Gujrat, and the imaging data were evaluated. The statistical kit for social science (spss) is used for data analysis. Results: out of 76 positive dengue patients there are 71(89.9%) male and 8(10%) are female .48 (60.8%) patients showed splenomegaly, 24(30%) patients showed ascites in which 8 (10%) have pelvic ascites and 16 (20.3%) abdominal ascites, 63 (79.7%) patients showed edematous GB wall thickening, 21(26.6%) showed pleural effusion while 18 (22.8 %) have bilateral pleural effusion and 3 (3.8%) have right sided. Conclusion: In patients presenting with fever and concomitant symptoms, sonographic signs of thickening GB wall, pleural effusion (bilateral or right side), ascites, and splenomegaly should strongly help in early diagnosis of dengue fever, especially during an outbreak.